Journalistic Construction of Reporting on Covid-19 in Online Media - Asisda Wahyu Asri Putradi; Abdul Muta’ Ali; Sonya P. Suganda (Journal La Sociale, 2024)
The Covid-19 pandemic is a global outbreak that has significantly changed people's social lives. The complexity of this issue has caused the coverage of Covid-19 to be dominant with negative news. Negative news can produce various psychological disorders that make readers avoid the news. The news media thus has a significant role in bridging society's adaptation to new patterns of life during the pandemic and adaptation to inconsistent government policies in dealing with the Covid-19 pandemic. Therefore, it is important for the news media to be able to bridge government policies with the psychological conditions of people affected by the pandemic. In this research study, constructive journalism can be one solution to overcome this problem. Through constructive journalism, the journalist's job is not only to focus on negative things but also on solutions and positive sides when covering news. Quantitative content analysis was used in this research by applying six elements of constructive journalism to 7 covid-19 articles published by CNN.com in 2020-2022. The research results show that news articles about Covid-19 on CNN.com are not constructive. All elements of constructive journalism found in these articles are below 50%. The element with the highest percentage found was The Rosling (47%) The lowest element found in covid-19 articles on CNN.com was the co-creation element at 9%.